2011
DOI: 10.1371/journal.pntd.0001309
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Viremia and NS1 Antigenemia Are Shaped by Immune Status and Virus Serotype in Adults with Dengue

Abstract: BackgroundDengue is a major public health problem in tropical and subtropical countries. Exploring the relationships between virological features of infection with patient immune status and outcome may help to identify predictors of disease severity and enable rational therapeutic strategies.MethodsClinical features, antibody responses and virological markers were characterized in Vietnamese adults participating in a randomised controlled treatment trial of chloroquine.ResultsOf the 248 patients with laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
205
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(233 citation statements)
references
References 41 publications
27
205
0
1
Order By: Relevance
“…Viremia levels were reported to decay faster during secondary infections. 18,20 However, this difference was observed regardless if the day of serum sample collection after fever onset was taken into consideration. Because of the small number of secondary infections (6.3%) detected, similar comparisons with DENV-1 patients were not possible.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Viremia levels were reported to decay faster during secondary infections. 18,20 However, this difference was observed regardless if the day of serum sample collection after fever onset was taken into consideration. Because of the small number of secondary infections (6.3%) detected, similar comparisons with DENV-1 patients were not possible.…”
Section: Resultsmentioning
confidence: 93%
“…18 Regarding a possible association between viremia levels and disease severity, conflicting results have been reported. Although several studies 12,19,20 reported a positive association between viremia levels and disease severity, other studies have not. 14,17 Because identification of markers for disease severity or increase risk of progression to the more severe forms of the disease is of major interest in dengue research, the aim of this study was to evaluate viremia and circulating NS1 levels in serum samples sera collected from patients in Mexico with dengue and to determine if the results obtained in the studies conducted in Asia may be reproduced in different epidemiologic and genetic settings.…”
Section: Introductionmentioning
confidence: 96%
“…The E protein specificity and diversity of PB-derived Abs may help to clear the mutating virus faster after secondary infection than after primary infection (11). It seems unlikely that these Abs have an impact on severity by enhancing infection, because the PB response peaks when viremia is already declining.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralizing Ab titers decline rapidly postinfection (10), and reactivation of specific memory B cells (MBCs) most likely contributes to protection after homologous infection. Moreover, cross-reactive MBCs might also be beneficial during heterologous infection, because they can lead to the production of large amounts of dengue-binding Abs, which, although not providing sterile protection, could positively influence the outcome of the disease by decreasing the virus load earlier in secondary cases compared with primary cases (11). In fact, serum from both primary and secondary patients is serotype cross-reactive in ELISA during the first weeks postinfection (6), and patients seem to be protected against all serotypes for a limited time (12), suggesting a potential protective role for the polyclonal Ab response generated during acute disease.…”
mentioning
confidence: 99%
“…As the samples studied were "day of admission samples" from adults, there may be some variation in the timing of the individual samples in relation to disease onset. The PCR methodology used here would be more sensitive for samples from very early after fever onset [18], while both NS1 and serological testing would be more sensitive for samples taken later after fever onset [19]. This would possibly account for the samples detected by PCR, but not by serology or NS1 testing (samples collected early after fever onset) and samples positive by serologic/NS1 but negative by PCR (samples collected later in the course of the fever).…”
Section: Discussionmentioning
confidence: 99%